Characterization of Dominant Hydrogen Bonded Complex Structures - P. Maharolkar, Aruna; Murugkar, A.G.; Patil, S.S.; Khirade, P.W. (Asian Journal of Chemistry, 2012)
The density (r), refractive index (nD), dielectric constant (es) and relaxation time (t) of binary mixture of allyl bromide (AB) with n-butanol including those of the pure liquids, were measured over the complete composition range at 283.15 K. The experimental data is used to calculate excess density (r)E, excess molar volumes (vmE), excess permittivity (esE), excess inverse relaxation time (1/t)E and Bruggeman factor. The excess parameters were fitted to Redlich-Kister equation. The variation of these parameters with composition and the effect of bonding in new chemical species were discussed from the point of view of intermolecular interactions in these mixtures. The decrease in excess molar volume (vmE) is attributed to the formation of hydrogen bonded associated species formed between unlike molecule.